2019
DOI: 10.1097/ppo.0000000000000374
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Autophagy in Renal Cell Cancer and the Associated Tumor Endothelium

Abstract: The clear cell subtype of kidney cancer encompasses most renal cell carcinoma cases and is associated with the loss of von Hippel-Lindau gene function or expression. Subsequent loss or mutation of the other allele influences cellular stress responses involving nutrient and hypoxia sensing. Autophagy is an important regulatory process promoting the disposal of unnecessary or degraded cellular components, tightly linked to almost all cellular processes. Organelles and proteins that become damaged or that are no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 209 publications
0
4
0
Order By: Relevance
“…The apparent defect in the ATG12-dependent conjugation system was associated with decrease autophagic flux, in accordance with the role for this ubiquitin-like protein conjugation system in autophagosome formation and expansion 38,39 . Considering the impact autophagy can have on cancer cells survival or dismiss 54 , targeting the autophagy process has been considered as potential therapeutic strategy to combat various type of tumors, including in patient with ccRCC [20][21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The apparent defect in the ATG12-dependent conjugation system was associated with decrease autophagic flux, in accordance with the role for this ubiquitin-like protein conjugation system in autophagosome formation and expansion 38,39 . Considering the impact autophagy can have on cancer cells survival or dismiss 54 , targeting the autophagy process has been considered as potential therapeutic strategy to combat various type of tumors, including in patient with ccRCC [20][21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, interventions to both stimulate and inhibit autophagy have been proposed as cancer therapies 19 . Likewise, inhibition and induction of autophagy have both been considered as therapeutic strategies to combat RCC [20][21][22][23][24] . Additional studies suggest that autophagic gene polymorphisms are associated with ccRCC risk and patient outcome 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“… 8 Recently, many reports have demonstrated that abnormal autophagy plays an important role in various malignant tumors, such as non‐small‐cell lung carcinoma, renal cell cancer, liver cancer, and colorectal cancer. 9 , 10 , 11 , 12 It has been demonstrated that autophagy plays an important role in the development of oral cavity carcinoma. For example, NKX2‐3, FADD, PARK2, and EGFR were identified as potential prognostic autophagy‐related markers during head and neck squamous cell carcinoma tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy dysregulation is involved in various human diseases, including tumors 8 . Recently, many reports have demonstrated that abnormal autophagy plays an important role in various malignant tumors, such as non‐small‐cell lung carcinoma, renal cell cancer, liver cancer, and colorectal cancer 9‐12 . It has been demonstrated that autophagy plays an important role in the development of oral cavity carcinoma.…”
Section: Introductionmentioning
confidence: 99%